(untitled) (Baghdad Science Journal, 2018)
Most pathological effects of lead on the body are due to ability of lead to bind with important cellular molecules of various tissues and organs leading to formation abnormal molecules and thus to emergence of pathological conditions. To evaluation the risk to the health status of Iraqi workers who work in the batteries industry, expression of three types of calmodulin related genes were examined. Blood samples were collected from worker working in Iraqi industry of batteries (located in Al-Waziriya), then RNAs extraction were done thereby gene expression for Calcium/Calmodulin- dependent protein kinase2 (CaMKK2), C-X-C Chemokine receptor 4 (CXCR4) and mitogen activated protein kinase kinase 6 (MAP2K6) was done for each sample by using RT-qPCR. The study showed that the expression of CXCR4 gene was significantly decrement in the lead exposed workers meanwhile the MAP2K6 gene insignificantly increment in those workers, but no effect appeared on their CaMKK2 gene expression. Conclusion obtained from this study is that lead has ability to impact on calmodulin related genes in the workers working in the batteries manufacture, but this ability is variable according to the type of gene.